2016
DOI: 10.7731/kifse.2016.30.5.060
|View full text |Cite
|
Sign up to set email alerts
|

Star Building Materials Study on Wood Structure and Combustion Characteristics

Abstract: This study investigated the structure and combustion characteristics of four species, Timber Douglas-fir being used construction materials (finishes), Lauan, Cryptomeria japonica, Pinus densiflora trees in the area. In lookong into the ignition characteristics was a time range of ignition (TTI) appeared in the 21 s~32 s, especially Pinus densiflora TTI is ignited in a relatively rapid 601 s to 21 s than the other materials were destroyed in the 631 s. The maximum heat release rate and average heat release rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Accordingly, this value is correlated more with the mean HRR than with the peak HRR. It can be said that materials that release energy relatively rapidly pose higher fire risks than those releasing energy slowly [20].…”
Section: Cone Calorimeter Testsmentioning
confidence: 99%
“…Accordingly, this value is correlated more with the mean HRR than with the peak HRR. It can be said that materials that release energy relatively rapidly pose higher fire risks than those releasing energy slowly [20].…”
Section: Cone Calorimeter Testsmentioning
confidence: 99%
“…시카고의 이로쿼이 극장 (1) 보스턴의 코코넛 그로브 나이트 , 클럽 (2) 한국의 씨랜드 청소년 훈련 센터 , (3) 및 대구 지하철역 화재 (4) (12) . 벽지의 연기밀도 및 연소특성에 대한 연구들도 수행되어 왔다.…”
Section: Introductionunclassified
“…Unlike Cryptomeria japonica, Pinus densiflora, they showed signs of carbonization at regular intervals. [8] Another previous study analyzed the fire vulnerability of MDF, OSB, cork board, and general wood plywood using a 45° Meckel's burner. As a result, the MDF greatly exceeded the char area of 5,000mm 2 , which is stipulated in Standard of the Nation Fire Agency of Republic Korea.…”
Section: Introductionmentioning
confidence: 99%
“…[13] According to previous studies, combustion characteristics were different for each tree species. [8] In addition, flame retardant treatment is actively implemented as a way to compensate for the fire vulnerability of wood. In addition, it was confirmed that eco-friendly fire retardant paint were being developed to escape environmental regulation when performing flame retardant treatment.…”
Section: Introductionmentioning
confidence: 99%